Innovation in Sustainable Construction Materials in Green Infrastructure Development - I Made Agus Mahendra (Yayasan Adra Karima Hubbi, 2024)
The construction industry significantly impacts environmental sustainability, prompting the need for innovative materials that minimize ecological footprints. Sustainable construction materials play a crucial role in the development of green infrastructure, aimed at enhancing urban resilience and promoting environmental conservation. This study aims to explore various innovative sustainable construction materials and their applications in green infrastructure projects. It seeks to identify the benefits and challenges associated with these materials in promoting eco-friendly building practices. A comprehensive literature review was conducted, analyzing recent advancements in sustainable construction materials, including recycled materials, bio-based composites, and smart materials. Case studies of successful green infrastructure projects utilizing these materials were examined to assess their effectiveness and sustainability. The findings reveal that innovative materials such as recycled concrete, bamboo, and mycelium composites significantly reduce carbon emissions and resource consumption. Case studies demonstrated improved energy efficiency and reduced waste in projects that employed these materials. Challenges related to cost, availability, and regulatory standards were also identified. The research concludes that the integration of innovative sustainable materials is vital for the advancement of green infrastructure. Emphasizing the benefits of these materials can lead to broader adoption in the construction industry. Future research should focus on overcoming the identified challenges and developing standardized guidelines to facilitate the use of sustainable materials in infrastructure projects